Odd-number cyclo[n]carbons sustaining alternating aromaticity - Baryshnikov, Gleb V.; Valiev, Rashid R.; Valiulina, Lenara I.; Kurtsevich, Alexandr E.; Kurtén, Theo; Sundholm, Dage; Pittelkow, Michael; Zhang, Jinglai; Ågren, Hans (The Journal of Physical Chemistry A)
Cyclo[n]carbons (n = 5, 7, 9,..., 29) composed from an odd number of carbon atoms are studied computationally at density functional theory (DFT) and ab initio complete active space self-consistent field (CASSCF) levels of theory to get insight into their electronic structure and aromaticity. DFT calculations predict a strongly delocalized carbene structure of the cyclo[n]carbons and an aromatic character for all of them. In contrast, calculations at the CASSCF level yield geometrically bent and electronically localized carbene structures leading to an alternating double aromaticity of the odd-number cyclo[n]carbons. CASSCF calculations yield a singlet electronic ground state for the studied cyclo[n]carbons except for C25, whereas at the DFT level the energy difference between the lowest singlet and triplet states depends on the employed functional. The BHandHLYP functional predicts a triplet ground state of the larger odd-number cyclo[n]carbons starting from n = 13. Current-density calculations at the BHandHLYP level using the CASSCFoptimized molecular structures show that there is a through-space delocalization in the cyclo[n]carbons. The current density avoids the carbene carbon atom, leading to an alternating double aromaticity of the oddnumber cyclo[n]carbons satisfying the antiaromatic [4k+1] and aromatic [4k+3] rules. C11, C15, and C19 are aromatic and can be prioritized in future synthesis. We predict a bond-shift phenomenon for the triplet state of the cyclo[n]carbons leading to resonance structures that have different reactivity toward dimerization.